(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Indian population is typically complex and diverse forits religious, cultural and socioeconomic diversities. The same is visible inschools in the post-independence era. Schools are bound to cater this diversitywith the spirit of secularism and unity. The role of a Principal comes out tofoster this diversity and inclusiveness in which an every individual child’seducation is successfully administered; basically six strategies are to beadopted by a Principal of a school with diversity. The present paper defineshow these strategies could successfully improve inclusiveness. The researcherwith his experience as a principal in a private school put all these strategiesin practice and finds them effective. The same have been supported by manyresearches.